Keramahan Kristen di Tengah Krisis: Menyikapi Isu Imigrasi Dan Pengungsi Dari Perspektif Kitab Imamat 19:33-34 - Lele, Aldorio Flavius (Jurnal Teologi Kontekstual Indonesia, 2024)
This study explores the concept of Christian hospitality in response to immigration and refugee issues with reference to Leviticus 19:33-34. In the context of a global crisis, churches and Christian communities are called to show hospitality to refugees and immigrants, reflecting a commitment to provide help, support, and compassion to fellow human beings in distress. This research utilizes a qualitative approach with an in-depth analysis of the biblical text, especially Leviticus 19:33-34, and includes understanding the values, principles, and views related to hospitality. The results illustrate that the concept of Christian hospitality is placed in the context of holiness, emphasizing the importance of loving and welcoming strangers as a response to divine authority. Its theological implications include spiritual identity formation and bearing witness to God's love, while its practical implications form the basis for inclusive social policies and moral education.